An Analysis of Idiomatic Expression in Short Story The Black Cat by Edgar Allan Poe And A Jury Of Her Peers by Susan Glaspell - VINCEN HALIM; Yusmalinda Yusmalinda (LINGUA LITERA : journal of english linguistics and literature, 2015)
The aim of this research was to find out the meanings of idiomatic expressions, the kinds of idiomatic expressions, and the dominant kinds of idiomatic expressions found in two short stories The Black Cat by Edgar Allan Poe and A Jury of Her Peers by Susan Glaspell. This study was a descriptive qualitative research. The sources of data in this research were words or phrases that are indicated as idioms found in short stories The Black Cat by Edgar Allan Poe and A Jury of Her Peers by Susan Glaspell. After analyzing the data, the writer found out three points. Firstly, the idioms found in the two short stories have different meanings from the meanings of its component parts. Secondly, there are five idiomatic expressions that are found in the two short stories. They are Intransitive Verbal Idiom, Transitive Verbal Idiom, Nominal Idiom, Adjectival Idiom, and Adverbial Idiom. Thirdly, after analyzing the five idiomatic expressions in the two short stories, the writer found that the dominant idiomatic expression is transitive verbal idiom that appears eighty one times in the short stories.